Literature Review. The acceptability of Moringa Leaf (Moringa Oleifera) enriched foods in Indonesia - Anisa Nur Rohman; Setyaningrum Rahmawaty (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Moringa leaves (Moringa oleifera) have many health benefits and have been used by the wider community to support health. The purpose of this review is to provide an overview of the acceptability of food products substituted with moringa leaves, based on studies conducted in Indonesia. Indosesia’s reference database, Garuda (Garba Rujukan Digital), was used for the eligible studies. The search terms used to obtain relevant studies were